Influence of heat transfer on the MHD stagnation point flow of a power law fluid with convective boundary condition - Jahan, S. (Penerbit UTM Press, 2015)
In this article, we examined the impact of heat transfer on the magnetohydrodynamic (MHD) stagnation point flow of a non-Newtonian power- law fluid with convective boundary condition. By using suitable similarity transformations, coupled nonlinear partial differential equations are transformed to ordinary differential equations. Then solved the resulting equations with Homotopy analysis method. Interesting flow parameters such as MHD M, stagnation parameter Î», convective parameter Î³ are discussed graphically. Convergence is checked at 20th order of approximation. Numerical values of physical interested parameter such as local Nusselt number are also tabulated. Â© 2015 Penerbit UTM Press. All rights reserved.